2006
DOI: 10.1093/jn/136.10.2481
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice Ellagitannin Metabolites Are Present in Human Plasma and Some Persist in Urine for Up to 48 Hours

Abstract: Ellagitannins (ETs) from pomegranate juice (PJ) are reported to have numerous biological properties, but their absorption and metabolism in humans are poorly understood. To investigate the pharmacokinetics of pomegranate ETs, 18 healthy volunteers were given 180 mL of PJ concentrate, and blood samples were obtained for 6 h afterwards. Twenty-four-hour urine collections were obtained on the day before (-1), the day of (0), and the day after (+1) the study. Ellagic acid (EA) was detected in plasma of all subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
384
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 402 publications
(406 citation statements)
references
References 26 publications
20
384
0
2
Order By: Relevance
“…Therefore, UA was studied in detail, since prior studies demonstrated that UA conjugates were the most prevalent metabolites of EA in human subjects and that they persist for up to 56 h after ingestion of ETs (9,10,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, UA was studied in detail, since prior studies demonstrated that UA conjugates were the most prevalent metabolites of EA in human subjects and that they persist for up to 56 h after ingestion of ETs (9,10,12).…”
Section: Discussionmentioning
confidence: 99%
“…An ET-enriched PE derived from the skin of pomegranate fruit (Punica granatum L., Wonderful Variety, Paramount Farms, Lost Hills, CA), was standardized to 37% ETs (as punicalagin isomers) and 3.5% free EA as reported (15). PE was administered to animals in doses based on the amount of ETs (as punicalagins) in a single serving of PJ (240 mL of single strength juice, ∼80 mg of ETs) (9). The equivalent dose that would be administered to a 70 kg human was calculated for a mouse of 25 g body weight to be 0.03 mg of ETs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first product of ellagic acid catabolism is urolithin D, and successive loss of hydroxy groups result in the formation of urolithins C, A, and B 3. All mammals seem able to produce urolithins from ellagitannins found in food 4, 5. In healthy humans, urolithins A and B are most abundant 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…All mammals seem able to produce urolithins from ellagitannins found in food 4, 5. In healthy humans, urolithins A and B are most abundant 5, 6. Urolithin A is the most reported analogue due to its anti‐oxidative and anti‐inflammatory properties in various tissues 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%